STRATEGI PENGEMBANGAN WISATA BAHARI BERDASARKAN ANALISIS KESESUAIAN DAN DAYA DUKUNG WISATA BAHARI DI PANTAI PENIDA (CRYSTAL BAY) - Maydayanti, Ni Kadek; Pujaastawa, Ida Bagus Gde; Adhika, I Made (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 18 No 2 (2024), 2024)
Crystal Bay is one of the favorite tourist destinations for foreign tourists. This research aims to determine the suitability of marine tourism for snorkeling, diving, and beach recreation activities, measure the carrying capacity of nautical tourism, and formulate a strategy for developing marine tourism on Penida Beach. The method used to analyze the suitability of marine tourism is the concept of suitability by Yulianda et al. 2010, analysis of environmental carrying capacity according to Cifuentes, and formulation of a maritime tourism development strategy through SWOT. The results of the study of the suitability of marine tourism carried out by Penida Beach are in the S2 category with an IKW of 66.75% for snorkeling and diving of 64.81% and the beach recreation tourism category with an IKW value of 81.11%. The physical carrying capacity analysis calculation at Penida Beach showed that permitted tourist visits were for diving tourism activities of 5,082 people per year, snorkeling activities of 1,545,291 people per year, and beach recreation of 103,092 people per year. Analysis of the actual carrying capacity was obtained at 2,730 people per year for diving activities, snorkeling activities at 736,826 people per year, and beach recreation activities at 99,999 people per year. The practical tourism carrying capacity calculation results are 1815 people per year, 508,563 for snorkeling and beach recreation activities, and 68,970 people annually. Marine tourism development strategies include carrying out beach clean-up activities, monitoring and monitoring coral reef ecosystems, providing diving equipment, public education, rubbish bins, changing rooms, showers, clean water, signage, information, and selling areas. Souvenirs and wave break buildings to support the Nusa Penida Festival Event. Maximizing awig - awig, patrol facilities to be carried out daily, additional security facilities, and restrictions on tourist visits. They are conducting outreach to the community, requesting funds for developing tourism facilities, providing information related to the MPA, English language training, and preserving awig - awig. Keywords: tourism suitability; carrying capacity; sustainable tourism; SWOT